(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Background: Motherhood is an integral part of womanhood and being childless is a devastating experience for a woman in developing countries like Bangladesh. Majority of patients in developing countries have virtually no access to treatment. Few health facilities have provision for proper diagnosis and treatment for infertility. There is a general lack of awareness among the public regarding infertility. In the quest for conception, many couples adopt for alternative therapies and religious rituals killing crucial age and time. Objective: To find out the treatment seeking behavior and the profile of infertile patients attending a tertiary infertility center at Dhaka, Bangladesh . Methods: During a period of five years from January 2001 to December 2005, 8580 new patients attending a tertiary infertility center at Dhaka were included in the study. Results: Treatment seeking behavior of infertile patients attending Center for Assisted Reproduction, (CARe) Dhaka revealed 30% of the patients initially go to the traditional healers for the relief of infertility, 36% consult both traditional healers and doctors and 32% consulted with GP and Gynae specialist, and only 2% came straight to the tertiary center( CARe) for their subfertility. 55% of the patients attending the clinic were from urban area and 45% were from rural area. The maximum number of patients were from Dhaka division followed by Chittagong, Khulna, Barisal, Sylhet and Rajshahi. The overall primary and secondary infertility were in 63.34% and 36.66% of the patients respectively. 90% of the patients were Muslim and 9% were Hindu and 1% were from other religion. Only 32.37 % of the patients took treatment in the clinic for their infertility. Male factor problems as identified among the male partners of the infertile couples were azoospermia in 18%, abnormal semen parameter in 24%,and normal semen parameter in 58 %. Among the female partners completing investigations, 17% suffered from anovulation, 20% from premature ovarian failure and 3% from ovarian failure , with a total of 40% of the women suffering from ovarian factor, 8% suffered from endometriosis, 7% from bilateral tubal block, 3% from uterine factor problem. In 42% women there was no apparent cause in the females. Untreatable causes of infertility among the infertile couples were in 3.75% of the patients. Ovarian failure was in 3% cases, testicular failure in 0.5% and uterine factor in 0.25% of cases. 75% of the women were less than thirty five years of age where as 29 % of the males were less than 35 years. Conclusion: Causes of infertility vary from region to region so also social and cultural conditions. Financial condition also affects the health seeking behavior of the patients. For the purpose of management of infertile couples the cause of infertility is important to understand so that the options of treatment and the prognosis can be discussed with the patients. J Bangladesh Coll Phys Surg 2016; 34(3): 140-144